Context dependent stated choice experiments: The case of train egress mode choice - Eric J. E. Molin; Harry J. P. Timmermans (Journal of Choice Modelling, 2010)
Based on the contention that the influence of context on mode choices made in multi-modal trip chains is under-researched, this paper discusses the design and results of a stated choice experiment to estimate the effects of context variables on train egress mode choice: the mode chosen after a train trip in order to reach the final destination. The results derived from a sample of 996 train travellers indicate that context variables, which were varied in the experiment (travel purpose, time of day, weather, travel party, amount of luggage, distance and route knowledge), all have significant effects on egress mode choice. Moreover, the estimated coefficients were all in anticipated directions, lending face validity to the results. Finally, the results indicate that context effects differ between some sociodemographic variables. In particular, there is evidence of strong gender differences.
Keywords: 330; stated choice; mode choice; multi-modal; context effects